Pengaruh Karakteristik Perusahaan Terhadap Audit Delay - Ni Nyoman Alit Triani; Shafa Alya Chairunnisah (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The impact of firm attributes including size, subsidiaries, audit firm size, leverage, profitability, and audit fees on audit delay is investigated in this study. The financial accounts of the company must be submitted on schedule, but in 2022, a number of corporations have not submitted their reports on time despite having been granted a grace period. This is the focus of the study so it needs to be studied further. Panel regression is used in this study to test the hypothesis using 1,180 sample data from three sectors of companies listed between 2018 and 2022 on the Indonesia Stock Exchange. The analysis's findings indicate that while firm size, subsidiaries, leverage, and audit fees have no effect on audit time, audit firm size and profitability do. This study contributes to academic research on company characteristics for reporting financial statements on time, especially in Indonesia. The results of this research can be used by users of financial reports in reviewing the effectiveness of company operations for continued investment and also useful for companies so that companies can be open about information and the accuracy of submitting financial reports. The new thing in this study is the use of samples of three company sectors that have the highest number of audit delay companies as the main focus of investors to invest their funds in these companies, so this study reflects the need for timeliness of financial reporting, especially for BEI listed companies.